Systems biology dissection of PTSD and MDD across brain regions, cell types, and blood - Daskalakis, Nikolaos P.; Iatrou, Artemis; Chatzinakos, Chris; Jajoo, Aarti; Snijders, Clara; Wylie, Dennis; DiPietro, Christopher P.; Tsatsani, Ioulia; Chen, Chia-Yen; Pernia, Cameron D.; Soliva-Estruch, Marina; Arasappan, Dhivya; et al. (Science (American Association for the Advancement of Science), 2024)
The molecular pathology of stress-related disorders remains elusive. Our brain multiregion, multiomic study of posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) included the central nucleus of the amygdala, hippocampal dentate gyrus, and medial prefrontal cortex (mPFC). Genes and exons within the mPFC carried most disease signals replicated across two independent cohorts. Pathways pointed to immune function, neuronal and synaptic regulation, and stress hormones. Multiomic factor and gene network analyses provided the underlying genomic structure. Single nucleus RNA sequencing in dorsolateral PFC revealed dysregulated (stress-related) signals in neuronal and non-neuronal cell types. Analyses of brain-blood intersections in >50,000 UK Biobank participants were conducted along with fine-mapping of the results of PTSD and MDD genome-wide association studies to distinguish risk from disease processes. Our data suggest shared and distinct molecular pathology in both disorders and propose potential therapeutic targets and biomarkers.